AKIBAT HUKUM DARI PEMBUATAN AKTA JUAL BELI YANG MENDAHULUI PROSES PEMECAHAN SERTIFIKAT TANAH MENURUT PERATURAN PEMERINTAH NOMOR 24 TAHUN 1997 TENTANG PENDAFTARAN TANAH (Studi Kasus Kantor Pejabat Pembuat Akta Tanah Muhamad Nur Kholis Muslim, SH., M.Kn.): AKIBAT HUKUM DARI PEMBUATAN AKTA JUAL BELI YANG MENDAHULUI PROSES PEMECAHAN SERTIFIKAT TANAH MENURUT PERATURAN PEMERINTAH NOMOR 24 TAHUN 1997 TENTANG PENDAFTARAN TANAH (Studi Kasus Kantor Pejabat Pembuat Akta Tanah Muhamad Nur Kholis Muslim, SH. - admin, Admin; Moh. Babur Rizki; Khusnul Hitaminah; Abdur Rohim (STIH Zainul Hasan Kraksaan Kraksaan, 2024)
Abstract The making of a deed of sale and purchase of land by a Land Deed Official (PPAT) originating from a parent land certificate must first be carried out by splitting the land certificate. However, in its application, PPAT MuhamadNurKholis Muslim, SH, M.Kn issued a deed of sale and purchase of land originating from the parent land certificate without preceding the splitting of the land certificate. This study aims to determine the legalconsequences of making a deed of sale and purchase of land that precedes the process of splitting the land certificate at the Office of PPAT MuhamadNurKholis Muslim, SH, M.Kn and the settlement process. This research is an empirical juridical research using a conflict approach, namely by analyzing the problems of making a deed of sale and purchase conducted through interviews and analysis of related documents. The results of this study explain that the sale and purchase deed made prior to the process of splitting the land certificate is an inappropriate procedure, the document does not contain correct information so that it does not have strong legal force. The settlement process is carried out by the relevant parties submitting the split of the main land certificate to the BPN Office of Probolinggo Regency and revising the sale and purchase deed to the PPAT concerned. With these problems, it is hoped that all PPATs will carry out their duties procedurally. Keywords: Deed, Sale and Purchase, Split, Land Certificate